KONTRIBUSI PENGELOLAAN, PENYIMPANAN DAN PENGHAPUSAN ARSIP TERHADAP LAYANAN PRIMA - IRAWATY ZAINAL, HENNY (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2013)
ABSTRACT The goal of this research is to describe and find out the contribution of archive management, storage, and removal to service excellence in PT Pacific Indo Packing. This research invloves 60 PT Pacific Indo Packing employees as the sample. The instruments used in this study are questionnaire, documentation, and interview. The result shows the correlation between archive management, storage, and removal and service excellence, it is shown by Fhitung = 4,796 >Ftabel = 2,79, shown Fhitung is bigger than Ftabel which means archive management, storage, and removal are strongly contributed to service excellece in PT Pacific Indo Packing. Key words: Management, Storage, Archive Removal, and Service Excellence